Perbandingan Super-Resolution dan CBAM untuk Optimasi Deteksi Objek Drone Termal - Helfy Susilawati; Akhmad Fauzi Ikhsan; Firman; Arief Suryadi Satyawan; Chandra Rahmana (This journal is published by the Department of Electrical and Information Engineering, Faculty of Engineering, Universitas Gadjah Mada., 2026)
Human detection using thermal cameras is very useful in certain conditions, such as detecting people lost in mountainous areas that are difficult to explore. Rescue operations are usually conducted by deploying a search and rescue (SAR) team to the location, which is not always effective because this operation can only be carried out under certain conditions and may pose a risk to the SAR team itself. Therefore, one alternative approach is the use of drones equipped with human detection and recognition capabilities. In this context, thermal cameras are used because they can penetrate challenging environments, making them suitable for SAR operations. The object detection method used in this study was You Only Look Once (YOLO) version 8 or YOLOv8. This study aimed to compare the effectiveness of integrating enhanced super-resolution generative adversarial networks (ESRGAN) with YOLOv8 and incorporating a convolutional block attention module (CBAM) into the neck architecture of YOLOv8. The performance of ESRGAN with YOLOv8 and CBAM with YOLOv8 was evaluated using precision, mean average precision (mAP), and training loss. Based on the experimental results, the combination of ESRGAN with YOLOv8 outperformed the CBAM-based modification. This is indicated by higher precision and mAP values, as well as lower training loss in the ESRGAN-enhanced YOLOv8 detection framework. The experimental findings highlight that image enhancement using ESRGAN is more effective than CBAM-based modification in improving thermal image-based human detection performance for SAR applications.